Editorial - Irfan A. Rather (Journal of Biological Insights, 2026)
The establishment of a new scholarly journal requires a clear articulation of goals and editorial standards. The Journal of Biological Insights (JBI) was established to offer a targeted and rigorous platform for the publication of excellent research in the biological sciences, with a focus on studies that promote conceptual clarity and mechanistic understanding. Biological research continues to expand; however, despite this expansion, maintaining methodological rigor, reproducibility, and depth of interpretation continues to present difficulties. Therefore, JBI prioritizes well-designed studies that provide significant biological insight over merely descriptive findings in an effort to address these issues.